Environmental disclosure: a study of Santa Catarina state potentially polluting (Revista Brasileira de Contabilidade e Gestão, 2016)
This study aims to evaluate the environmental performance of a potentially polluting industrial company's disclosure of the state of Santa Catarina. To achieve this goal, we adopted a research case study, descriptive in nature type, with qualitative and documentary approach to problem regarding the technical procedures. Data were collected in the 2013 Sustainability Report of the company. It was applied the model Environmental Disclosure Evaluation (EDE), consisting of 103 criteria divided into four clusters: (i) environmental management, (ii) consumption of natural resources; (iii) emissions, effluents, waste and impacts; and (iv) legal compliance and financial aspects. The model is based on the Global Reporting Initiative (GRI) and created from the Multicriteria Methodology for Decision Support Constructivist (MCDA-C). As an overall result, it was found that the average rate performance achieved by the company was 31.23 points representing considered "moderate." There was a greater commitment of the company with information on the areas of environmental management, natural resource consumption, emissions and waste, items valued with "strong/moderate" performance. It found a "low" performance criteria for wastewater, and transportation products; and "null" for biodiversity and legal compliance items.
Keywords: environmental disclosure; sustainability report; performanace assessment